The Impact of Social Factor on Decision Making in TB Patients: An Approach to Consumer Behavior in Health Sector - Yenny Purwanti; Auli Fisty Noor Azizah; Djazuly Chalidyanto; Ernawaty Ernawaty (Humanistic Network for Science and Technology (HNST), 2018)
Tuberculosis is commonly shortened to TB is still a health problem throughout the world, including in Indonesia. Treatment loss rate (loss to follow-up) treatment of pulmonary TB nationally is estimated to be high, this is very dangerous because treatment that is done irregularly will have a worse effect than not done at all. Treatment loss (loss to follow-up) treatment TB in Pasuruan district is 3.50%, although it does not exceed the national target of > 10%, it should not be ignored, because there are several Public health centers with loss to follow-up treatment for TB treatment> 10% in two consecutive years. This study aims to analyze the social factors that influence the decision making of TB treatment which is the cause of the drop out of treatment. This study was a cross sectional study conducted in 4 Public health centers in Pasuruan, namely Bangil Health Center, Pandaan Health Center, Gempol Health Center, and Kejayan Health Center with a sample size of 66 TB patients. Data analysis using multiple logistic regression. Based on the results of the study it was found that social factors that influence decision making were only family members (p = 0.037, Exp B = 4.558). Whereas other social factors, namely the reference group and leader opinion, have no effect with p = 0.813 and p = 0.939. Therefore, the role of family members should be carried out on the grounds of being more trustworthy, in addition to the closeness of the emotional relationship that greatly affects TB patients. Keywords: TB, loss to follow up, social factors, decision making